Bisnis Multi Level Marketing (MLM) dalam Perspektif Fiqih Muamalah - Ardiansyah, Andri; Hidayanti, Sri; Andika; Hafid, Ridho Agni; Putri, Junita Ahira (Jurnal Indragiri Penelitian Multidisiplin, 2024)
This research emphasizes the importance of examining the Multi Level Marketing (MLM) business model from the perspective of Islamic law, especially fiqh muamalah. The research found that the structure and operational mechanisms of MLM often trigger injustice, and uncertainty, as well as potential violations of sharia principles such as gharar, riba, and maysir. In Islamic teachings, the principles of fairness, transparency and certainty are things that must be maintained in every economic transaction. This study reveals that many MLM models tend to focus more on recruiting new members rather than selling real products, which can result in unfairness in profit sharing. To ensure that MLM complies with sharia principles, companies should design a fair and balanced commission structure, ensure every transaction is conducted transparently, and offer products that have real benefits and clear selling points. This research has important implications for business actors, regulators, and the wider community. Strict regulations and effective supervision are needed to ensure that MLM business practices are fair and transparent. This research underscores the need for commitment from all parties involved, including companies, members, and sharia authorities, to maintain the principles of fairness, transparency, and certainty in every MLM business transaction. Thus, the MLM business model can run in accordance with Islamic law and make a positive contribution to the economy of Muslims.